2008
DOI: 10.1262/jrd.20028
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Kaempferia parviflora did not Disturb Male Reproduction in Rats

Abstract: Abstract.To investigate the androgenic effect of Kaempferia parviflora (KP), a Thai herbal plant, adult male rats were randomized into control and KP-treatment groups. Rats were treated orally with water in the control group and with 1,000 mg/kg/day of KP in the treatment group for 45 days. Blood samples were collected on days 10, 20, 30 and 45 for measurement of the serum follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone, progesterone and corticosterone levels. The reproductive and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…These results also indicated that KP treatment at 420 mg/kg could improve the testes weight and sperm concentration. Previous studies reported that KP treatment at 1,000 mg/kg for 45 consecutive days in normal rats showed no significant impact in term of the reproductive and nonreproductive organ weight compared to nontreatment rats (Trisomboon et al., ). KP treatment in castrated immature rats also showed no significant impact in relative reproductive and nonreproductive organ weight compared with nontreatment rats (Trisomboon, Watanabe, Wetchasit, & Taya, ).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…These results also indicated that KP treatment at 420 mg/kg could improve the testes weight and sperm concentration. Previous studies reported that KP treatment at 1,000 mg/kg for 45 consecutive days in normal rats showed no significant impact in term of the reproductive and nonreproductive organ weight compared to nontreatment rats (Trisomboon et al., ). KP treatment in castrated immature rats also showed no significant impact in relative reproductive and nonreproductive organ weight compared with nontreatment rats (Trisomboon, Watanabe, Wetchasit, & Taya, ).…”
Section: Discussionmentioning
confidence: 93%
“…KP treatment in castrated immature rats also showed no significant impact in relative reproductive and nonreproductive organ weight compared with nontreatment rats (Trisomboon, Watanabe, Wetchasit, & Taya, ). Several studies have reported that KP treatment may also elevate serum testosterone and the hormone could increase the reproductive organ weight (Chaturapanich, Chaiyakul, Verawatnapakul, Yimlamai, & Pholpramool, ; Trisomboon et al., ). Furthermore, our results are in agreement with those of previous reports, showing that KP treatment in diabetic rats increase serum testosterone level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9) The extract of the rhizomes of K. parviflora and its constituents were revealed to exhibit several pharmacological activities, such as antiplasmoidal, antifungal, 2) antiinflammatory, [10][11][12] α-glucosidase inhibitory, 13) and xanthine oxidase inhibitory 1) activities and cytotoxicity of several tumor cell lines 14,15) as well as effect of P-glycoprotein function 16) and modulation of multi-drug resistance in cancer cells.…”
mentioning
confidence: 99%